Mahirap Pero Kinakaya: A Sequential Exploratory Inquiry on the Experiences of Multigrade Teachers - Hermosa, Gina D.; Sanchez, Geremy G. (Future Science / FSH-PH Publications, 2025)
This study examined the challenges and coping strategies of multigrade teachers in the Suyo District. The goal was to suggest policy actions that could improve teaching and learning in rural schools. The research used a sequential exploratory mixed-methods design. It started with qualitative interviews to identify common themes and then conducted a quantitative survey to confirm and expand upon the findings. Results showed eight major challenges: (1) time management, (2) curriculum demands, (3) instructional difficulties, (4) lack of instructional materials, (5) classroom management issues, (6) learner diversity, (7) limited parental support, and (8) insufficient professional development. The quantitative analysis confirmed that the three most pressing concerns were learner diversity, curriculum complexity, and insufficient professional development, as these showed the highest levels of seriousness among respondents. Teachers tackled these issues using coping strategies in eight areas: time management, instructional flexibility, differentiated instruction, resourcefulness, classroom management skills, adaptive teaching, peer school support, and participation in professional development. The study concluded that multigrade instruction is a viable way to ensure equal education when teachers receive enough support from institutions and the community. It recommends creating a multigrade-specific curriculum framework, strengthening peer mentoring and Learning Action Cells (LACs), improving professional learning programs, enhancing access to teaching resources, and increasing community and parental involvement.